The Influence of Motivation and Discipline on Employee Performance at the Ambon Industrial Services and Standardization Center - Rahawarin, Mohamad Arsad; Ohoitimur, Ivoni; Ohoiwutun, Stanislaus Kostka (LPPM Institut Pendidikan Nusantara Global, 2025)
This research aims to examine the effect of motivation and discipline on the performance of employees at the Center for Standardization and Industrial Services (BSPJI) Ambon. A quantitative research method was employed, with a total population of 40 employees from BSPJI Ambon. The study utilized a saturated sampling technique, meaning all members of the population were included as samples. Data analysis was conducted using multiple linear regression. The findings reveal that: (1) Motivation significantly influences employee performance at BSPJI Ambon; (2) Discipline also has a significant impact on employee performance at BSPJI Ambon; (3) Together, motivation and discipline significantly affect employee performance at BSPJI Ambon.